The Challenges of Food Security Policy in Indonesia: Lesson Learned from Vietnam, India, and Japan - Widiana, Anika; Wijaya, Chandra; Atmoko, Andreo Wahyudi (Technium Social Sciences Journal, 2022)
Food security is a fundamental issue for a country or state. In Indonesia, there are still many problems related to food, ranging from production to distribution problems. Indonesia’s national food consumption is still dominated by grains, so its availability becomes important for the community. In this article, case studies on the availability and food security issues from three selected countries (Vietnam, India and Japan) are presented. Vietnam is one of the ASEAN members that has successfully built its food industries. Over the last thirty years, Vietnam has transformed from a food crisis country to a food-secure country. Meanwhile, India is a large and populous country that has built institutional systems in order to establish its national food policy. Other more advanced lessons are from Japan, which has developed its agriculture industry to achieve food security and sovereignty. Japan has successfully developed advanced technology in its agriculture and food industries. The technology is generated through synergy between the government, the private sector, and university, and reasonable to be implemented. Indonesia could learn important lessons from the three countries, particularly in building systems and institutions to manage food supplies (rice) and distribution channels. In addition, the Indonesian government should encourage the development of technology, such as to build data, improve the productivity and quality of the food, as well as the distribution system. By working on this, food policy making and implementation to achieve food security and sustainability will be effective and efficient.